Implementasi Program Kartu Smart Madani di Dinas Komunikasi Informatika Statistik dan Persandian Kota Pekanbaru - Fadil Agustiansyah; Febri Yuliani (Peneliti.net, 2022)
The madani smart card program is a policy made by the Pekanbaru City Government and the Communication Information Statistics and Coding Office of Pekanbaru City was appointed to be the leader in the implementation of this program. This program is based on Pekanbaru Mayor Regulation Number 194 of 2017 concerning the Utilization of Madani Smart Cards as Media for Access to Public Services. The Communication Information Statistics and Coding Office of Pekanbaru City cooperates with Bank BNI Pekanbaru as the party that issues and distributes smart civil cards to the public. The purpose of this study was to see the process of implementing the smart card program at the Communication Information Statistics and Coding Office of Pekanbaru City. The research method used is qualitative. Data collection techniques were carried out by observation, documentation and interviews. The results of the study found that the implementation carried out by the Communication Information Statistics and Coding Office of Pekanbaru City had not run optimally, in the process there were still obstacles that caused this program to not run optimally.